Relatório final do estágio curricular em prática veterinária, realizado junto à Clínica Veterinária da UNIFRAN em Franca - SP, e ao Hospital Veterinário da UNIUBE em Uberaba – MG. Caso de interesse: Uretrostomia pré-púbica após ruptura traumática de uretra membranosa em cão. - Pires, Caroline Plez [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
O presente relatório refere-se às atividades desenvolvidas pela discente Caroline Plez Pires, graduanda do décimo semestre do curso de bacharelado de Medicina Veterinária da Faculdade de Ciências Agrárias e Veterinárias – FCAV Unesp, Campus de Jaboticabal, sob orientação da Profa. Dra. Paola Castro Moraes no período de estágio curricular obrigatório. O mesmo foi desenvolvido na área de Clínica Cirúrgica de Pequenos Animais, em dois locais distintos: Clínica Veterinária da Universidade de Franca, localizada em Franca / SP e Hospital Veterinário da Universidade de Uberaba, localizada em Uberaba / MG.

This report refers to the activities developed by student Caroline Plez Pires, graduating from the tenth semester of the Bachelor's degree in Veterinary Medicine at the Faculty of Agricultural and Veterinary Sciences – FCAV Unesp, Jaboticabal Campus, under the guidance of Prof. Dr. Paola Castro Moraes during the mandatory curricular internship period. It was developed in the Small Animal Surgical Clinic area, in two different locations: the Veterinary Clinic of the University of Franca, located in Franca / SP and the Veterinary Hospital of the University of Uberaba, located in Uberaba / MG.
Final report of the curricular internship in veterinary practice, carried out at the UNIFRAN Veterinary Clinic in Franca - SP, and at the UNIUBE Veterinary Hospital in Uberaba - MG. Case of interest: Prepubic urethrostomy after traumatic rupture of the membranous urethra in a dog.
Keywords: Cirurgia veterinária; Uretra; Trauma